Assessing the impact of the united states people Republic of China trade dispute using a multiregional computable general equilibrium model. - Gentile,Elisabetta (ADB economics working paper series, 2020)
This paper quantifies the cost of the trade dispute that started in 2017 between the United States and the Peoples Republic of China for the countries involved and the global economy.The paper uses a computable general equilibrium model based on the 2017 Asian Development Bank Multiregional Input-Output Tables. It simulates a scenario based on the bilateral measures implemented as of May 2019 and a scenario based on additional 25% tariffs on all bilateral imports. It looks at effects on GDP, employment, consumption, and investment in both economies. It also notes trade diversion to other Asian economies, with Japan, Malaysia, the Republic of Korea, and Viet Nam benefiting the most.